High-temperature and transcritical heat pump cycles and advancements: A review. (October 2022) - Adamson, Keri-Marie; Walmsley, Timothy Gordon; Carson, James K.; Chen, Qun; Schlosser, Florian; Kong, Lana; Cleland, Donald John
Abstract: Industrial and large-scale heat pumps are a well-established, clean and low-emission technology for processing temperatures below 100 °C, especially when powered by renewable energy. The next frontier in heat pumping is to extend the economic operating envelope to supply the 100–200 °C range, where an estimated 27% of industrial process heat demand is required. Most high-temperature heat pump cycles operate at pressures below the refrigerant's critical point. However, high-temperature transcritical heat pump (HTTHP) technology has - due to the temperature glide – a significant efficiency potential, especially for processes with large temperature changes on the sink side. This review examines how further developments in HTTHP technology can leverage innovations from high-temperature heat pump research to respond to key technical challenges. To this end, a comprehensive list of 49 different high temperature or transcritical heat pump cycle structures was compiled, which lead to classification of 10 performance-enhancing cycle components. Focusing specifically on high-temperature transcritical heat pump cycles, this review establishes six technical challenges facing their development and proposes solutions for each challenge, including a new transcritical-transcritical cascade cycle innovation. A key outcome of the review is the proposal of a new cycle that requires detailed investigation as a candidate for a high-temperature transcritical heat pump cycle. Highlights: Establishes industrial heat pumps as an essential to fossil fuel phase-out. Identifies and classifies 49 high temperature or transcritical heat pump cycles. Classifies 10 approaches to heat pump cycle performance advancement. Analyses 6 challenges facing high-temperature transcritical cycle development. Proposes a new high-temperature transcritical heat pump cycle cascade.